2014
DOI: 10.1371/journal.pone.0087099
|View full text |Cite
|
Sign up to set email alerts
|

Affinity Improvement of a Therapeutic Antibody by Structure-Based Computational Design: Generation of Electrostatic Interactions in the Transition State Stabilizes the Antibody-Antigen Complex

Abstract: The optimization of antibodies is a desirable goal towards the development of better therapeutic strategies. The antibody 11K2 was previously developed as a therapeutic tool for inflammatory diseases, and displays very high affinity (4.6 pM) for its antigen the chemokine MCP-1 (monocyte chemo-attractant protein-1). We have employed a virtual library of mutations of 11K2 to identify antibody variants of potentially higher affinity, and to establish benchmarks in the engineering of a mature therapeutic antibody.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 44 publications
4
53
0
Order By: Relevance
“…By combining successful mutations, the affinity for type 4 was enhanced by more than two orders of magnitude without reducing affinity for other serotypes. Most of the successful mutations were charged or polar, and located at the periphery of the binding interface, which is generally consistent with findings from other studies (2224, 26). This exciting study highlights the potential of using design methods to achieve unique binding specificities that are difficult to achieve using conventional discovery methods.…”
Section: Antibody Binding Affinity and Specificitysupporting
confidence: 90%
See 1 more Smart Citation
“…By combining successful mutations, the affinity for type 4 was enhanced by more than two orders of magnitude without reducing affinity for other serotypes. Most of the successful mutations were charged or polar, and located at the periphery of the binding interface, which is generally consistent with findings from other studies (2224, 26). This exciting study highlights the potential of using design methods to achieve unique binding specificities that are difficult to achieve using conventional discovery methods.…”
Section: Antibody Binding Affinity and Specificitysupporting
confidence: 90%
“…More generally, these findings are consistent with other studies revealing that the likelihood of identifying beneficial mutations is higher outside the initial binding interface (2427), likely due to the reduced risk of disrupting existing antibody–antigen interactions. This (22) and related work (2426, 28, 29) have demonstrated the potential of using existing methods for calculating electrostatic interactions to identify mutations that improve antibody affinity.…”
Section: Antibody Binding Affinity and Specificitymentioning
confidence: 94%
“…The thermodynamic analysis suggested that the relatively moderate DH and unfavorable DS may account for the moderate binding affinity. The thermodynamic parameters were compared with those of antibodies [30][31][32][33][34] and immune cell receptors [35][36][37] ( Table 4). Among antibodies, the 2F4-scFv exhibited relatively smaller DG, but similar level of DG with those for binding of cell surface receptors to ligands (5.9-7.2 kcalÁmol À1 ) ( Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of H3 structures is therefore extremely useful, enabling predictions to be made about antibody binding properties and hence their suitability as drugs (Clark et al , 2006; Diskin et al , 2011; Kiyoshi et al , 2014; Kuroda et al , 2012; Krawczyk et al , 2013; Lewis et al , 2014; Lippow et al , 2007; Thakkar et al , 2014). …”
Section: Resultsmentioning
confidence: 99%